Impact of chronic kidney disease on postoperative outcome following colorectal cancer surgery. (November 2014) - Currie, A.; Malietzis, G.; Askari, A.; Nachiappan, S.; Swift, P.; Jenkins, J. T.; Faiz, O. D.; Kennedy, R. H.
Abstract Aim Chronic kidney disease (CKD) is increasing in prevalence and is associated with cardiovascular events and mortality in asymptomatic and vascular surgery populations. This study aimed to determine the role of CKD in stratifying peri‐ and postoperative risk for colorectal cancer (CRC) patients with nonmetastatic disease undergoing elective curative resection. Method Patients diagnosed with nonmetastatic colorectal adenocarcinoma and undergoing surgical resection between 2006 and 2011 were identified from a prospectively collated database. Further information on survival and cause of death was gathered from a regional cancer registry. Estimated glomerular filtration rates were calculated using the Modification of Diet in Renal Disease (MDRD) equation. Kaplan–Meier survival curves were constructed for disease‐free and overall survival. Multivariate Cox regression models were used to determine the role of CKD after stratification by several clinicopathological factors. Results Seven‐hundred and eight colorectal resections were studied [median follow up: 45 (interquartile range, 21–65) months). Overall postoperative complications were similar, but patients with CKD were more likely to develop cardiovascular morbidity (P < 0.001) and 30‐day mortality [4.8% (six of 124) in the CKD group vs 2.1% (12/580) in the non‐CKD group]. Kaplan–Meier analysis revealed poorer overall survival for localized (Stage I–II; P = 0.019) and Stage III (P = 0.001) CRC in the CKD population. Multivariate Cox regression analysis identified CKD as an independent prognostic factor for noncancer death [hazard ratio (HR) = 1.82 (95% CI: 1.07–3.10); P = 0.027] but not for overall survival [HR = 1.21 (95% CI: 0.90–1.47); P = 0.116]. Conclusion Patients with CKD may be more likely to develop cardiovascular complications following CRC resection and have an increased risk of a noncancer death. Future research should explore the interaction of CKD in competing mortality risks following CRC surgery.